THE IMPACT OF SOCIAL MEDIA MARKETING ACTIVITIES ON SKINTIFIC PRODUCTS: PLS-SEM APPROACH - Afifah, Nanda Nasywa; Utari, Dina Tri (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
The swift expansion of the internet has markedly facilitated communication, thereby evolving social media from a tool for personal interaction into a formidable platform for product promotion. This research aims to investigate the effects of social media marketing endeavors on brand awareness, brand image, and brand loyalty about Skintific, a well-regarded skincare brand. Considering its growing significance, formulating a robust marketing strategy—especially within social media—is essential for enhancing brand visibility and cultivating customer loyalty. This study analyzes data from online questionnaires collected from June to July 2024 using Structural Equation Modeling (SEM) through Partial Least Squares (PLS). The sample for this investigation comprises 170 consumers of Skintific residing in Yogyakarta, with data gathered through questionnaires disseminated on platforms including Instagram, Twitter, LINE, and WhatsApp. The results indicate a positive and statistically significant correlation between social media marketing activities and brand metrics: awareness, image, and loyalty.